Clarithromycin Inhibits NF-κB Activation in Human Peripheral Blood Mononuclear Cells and Pulmonary Epithelial Cells - Ichiyama, Takashi (American Society for Microbiology, 2001)
Macrolide antibiotics modulate the production of proinflammatory cytokines in vivo and in vitro. Transcription of the genes for these proinflammatory cytokines is regulated by nuclear factor κB (NF-κB). We examined whether or not clarithromycin inhibits the activation of NF-κB induced by tumor necrosis factor alpha (TNF-α) or staphylococcal enterotoxin A (SEA) in human monocytic U-937 cells, a T-cell line (Jurkat), a pulmonary epithelial cell line (A549), and peripheral blood mononuclear cells (PBMC). Flow cytometry revealed that clarithromycin suppresses NF-κB activation induced by TNF-α in U-937 and Jurkat cells in a concentration-related manner. Western blot analysis also demonstrated that clarithromycin inhibits NF-κB activation induced by TNF-α in U-937, Jurkat, and A549 cells and PBMC and by SEA in PBMC. Western blot analysis of cytoplasmic extracts of A549 cells revealed that this inhibition is not linked to preservation of expression of the IκBα protein. The chloramphenicol acetyltransferase assay indicated that NF-κB-dependent reporter gene expression is suppressed in U-937 cells pretreated with clarithromycin. These findings are consistent with the idea that clarithromycin suppresses the production of proinflammatory cytokines via inhibition of NF-κB activation.